2013
DOI: 10.1038/cddis.2012.203
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative role of RanBP9 and P73 in mitochondria-mediated apoptosis

Abstract: Mitochondrial dysfunction and synaptic damage are critical early features of Alzheimer's disease (AD) associated with amyloid b (Ab) and s. We previously reported that the scaffolding protein RanBP9, which is overall increased in AD, simultaneously promotes Ab generation and focal adhesion disruption by accelerating the endocytosis of APP and b1-integrin, respectively. Moreover, RanBP9 induces neurodegeneration in vitro and in vivo and mediates Ab-induced neurotoxicity. However, little is known regarding the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 49 publications
2
58
1
1
Order By: Relevance
“…Stable RanBPM downregulated cells showed increased protein levels of anti-apoptotic Bcl-2 family members Bcl-2 and Bcl-X L and, following IR treatment, decreased mitochondrial localization of Bax, a pro-apoptotic Bcl-2 family member responsible for mitochondrial permeabilization and cytochrome-c release, a central step in the activation of apoptosis through the intrinsic pathway [5,86]. A later study confirmed that overexpression of RanBPM resulted in decreased Bcl-2 protein levels and increased Bax oligomerization [87]. This study also demonstrated that cells overexpressing RanBPM had increased mitochondrial membrane permeability and increased cytoplasmic cytochrome-c compared with control cells, demonstrating that RanBPM overexpression induces mitochondrial membrane depolarization resulting in the activation of apoptosis.…”
Section: Functionsmentioning
confidence: 99%
“…Stable RanBPM downregulated cells showed increased protein levels of anti-apoptotic Bcl-2 family members Bcl-2 and Bcl-X L and, following IR treatment, decreased mitochondrial localization of Bax, a pro-apoptotic Bcl-2 family member responsible for mitochondrial permeabilization and cytochrome-c release, a central step in the activation of apoptosis through the intrinsic pathway [5,86]. A later study confirmed that overexpression of RanBPM resulted in decreased Bcl-2 protein levels and increased Bax oligomerization [87]. This study also demonstrated that cells overexpressing RanBPM had increased mitochondrial membrane permeability and increased cytoplasmic cytochrome-c compared with control cells, demonstrating that RanBPM overexpression induces mitochondrial membrane depolarization resulting in the activation of apoptosis.…”
Section: Functionsmentioning
confidence: 99%
“…RanBP9 stabilizes p73 at the transcriptional and posttranslational level via physical interaction. 41 Furthermore, the ability to stimulate expression of the death receptors CD95, tumor necrosis factor (TNF)-R1, TRAIL-R1 and TRAIL-R2 as well as the caspases-3, -6 and -8 suggests that p73 is also involved in the extrinsic apoptosis pathway. 10,12 Induction of p73-dependent programmed cell death following DNA damage also involves endoplasmic reticulum stress and upregulation of scotin, a putative transmembrane protein able to colocalize with endoplasmic reticulum heat-shock proteins, such as GRP94.…”
Section: Cancer-fighting Properties Of Tap73mentioning
confidence: 99%
“…KIDINS220 interacts with RanBP9, a molecule critical for functioning of death domain [14]. RanBP9 is proved to be a pro-apoptotic protein in other cells as well [15]. …”
Section: Resultsmentioning
confidence: 99%